Information asymmetry and debt sustainability - Leite, João Pedro Rudge (2019)
Bulow and Rogoff (1989) proved that, in a competitive financial market, the threat of credit exclusion alone cannot sustain repayment of sovereign debt, as the defaulting government can still enter cash-in-advance insurance contracts. Phan (2016) extended the analysis to the case where the government has some private information about the underlying distribution of future economic shocks. He proved that, in a strategic environment where a sovereign trades with several competing foreign investors, there exists a perfect Bayesian equilibrium with signaling where a high type government repays some positive level of debt while the low type government prefers to default. The objective of this paper is to push forward the analysis in Phan (2016) in several directions. We first make a thorough analysis of the properties of the stationary value function and provide a rigorous proof of existence of a positive self-enforcing and not-too-tight debt limit in the model of Phan (2016). We then show that the repayment incentives at the endogenous debt limit are the same for both types of government. Finally, we refine the equilibrium concept in Phan (2016) by requiring investors’ beliefs to be consistent with the government’s strategies along the equilibrium path (as in Phan (2016)) but also out-of-equilibrium paths. We show that our refined equilibrium exists only if investors’ belief about the government’s future income is not too optimistic.